LADDER TO LEADERSHIP: A STUDY ON CHALLENGES FACED BY WOMEN IN HEIS IN INDIA - Chandan, Komakshi; Maini, Arti (The journal of contemporary issues in business and government, 2023)
Purpose-The purpose of this paper is to report certain factors which challenges women to take up leadership positions in HEIs. Although many studies examine women’s inclusion in the world, still there is a lack of studies regarding women in leadership positions in Indian Higher Educational Institutions. This paper aims at gaining an insight into certain organisational, societal and personal factors which challenges women to take up senior positions in HEIs Design/methodology/approach-This research was done using semi-structured interviews with women academicians who are working in HEIs in India. Findings- It was quite evident during the research that women in academics are somewhat excluded from various opportunities due to certain factors such as organisational, societal and personal factors. The majority of the participants in the survey did not believe that men are better at holding up top leadership positions in academia or any other organizations. The research results in this paper suggest that there are factors that women academicians encounter in HEIs and their impact on their career development. Implications- This study looked into the perception of female academicians towards women inclusion in leadership roles in higher educational institutions. Overall, the interviews suggested that females experienced a number of challenges that could have an impact on their job obligations and ability to work in the HEIs. Originality/value-This paper found the barriers to women’s advancement, especially in academic institutions.